RISKS ANALYSIS OF RAIL ENTERPRISES IN THE CONDITIONS OF CURRENT CHALLENGES (Development Service Industry Management, 2025)
The aim of the article is to analyze the risks of rail enterprises in the conditions of full-scale military aggression of the Russian Federation against Ukraine and to identify tools to reduce their negative impact on the activities of enterprises. It is shown that rail enterprises in the current conditions are faced with a significant increase in instability, which is formed in their internal and external environments and leads to the emergence of new risks and threats. Eight main risks currently faced by rail enterprises are identified and analyzed, namely the risk of physical destruction of rail infrastructure, the risk of disruptions in the supply of resources, threats to the safety of enterprise employees, risks of disruption of supply chains, cyber threats, environmental risks, risks of the legal and regulatory environment, and the risk of financial instability. It is determined that the physical destruction of rail infrastructure in conditions of military conflict constitutes a critical systemic risk that disrupts transport connections, destabilizes logistics chains, causes significant economic losses, and complicates strategic planning for industry recovery. It is shown that the risk of disruptions in the supply of critical resources significantly undermines the technical and operational sustainability of rail transport in conditions of armed conflict, requiring the implementation of adaptive logistics strategies, diversification of supply sources, and digital monitoring to strengthen national security. It is substantiated that disruption of supply chains in conditions of martial law and geopolitical instability poses a systemic threat to rail transport, causing delays in strategic cargo, financial losses, and strain on infrastructure, requiring digital, route, and international adaptation of logistics solutions. It is shown that the financial instability of rail enterprises in modern conditions undermines the efficiency of their operational activities, investment capacity and ability to modernize.
Keywords: threat; risk; analysis; activity; rail enterprise; efficiency; unstable environment